The Role of IFT140 in Osteogenesis of Adult Mice Long Bone. (August 2019) - Tao, Dike; Xue, Hui; Zhang, Chenyang; Li, Gongchen; Sun, Yao
Primary cilia have a pivotal role in bone development and the dysfunctions of primary cilia cause skeletal ciliopathies. Intraflagellar transport (IFT) proteins are conserved mediators of cilium signaling. IFT sub-complex A is known to regulate retrograde IFT in the cilium. As a core protein of IFT complex A, IFT140 has been shown to have a relationship with serious skeletal ciliopathies caused in humans. However, the effects and mechanisms of IFT140 in bone formation have not been systematically disclosed. To further investigate the potential role of IFT140 in osteogenesis, we established a mouse model by conditional deletion of IFT140 in pre-osteoblasts. The adult knock-out mice exhibited dwarf phenotypes, such as short bone length, less bone mass, and decreased bone mineral apposition rate. In addition, by IFT140 deletion, the expressions of several osteoblastic markers were decreased and loss of bone became severe with aging. These results suggest that cilia gene Ift140 is essential in bone development.